Pengaruh Status Sosial, Kualitas Produk, Dan Kepuasan Konsumen Terhadap Minat Beli Ulang Kopi Susu Baper Di Kota Metro - Selamet Fuadi; Yateno; Esza Reymitha (Jurnal Manajemen DIVERSIFIKASI, 2024)
Repurchasing from consumers is a matter of great concern to a company, where to make this happen the company must pay attention to several factors related to this behavior. Repurchasing behavior of consumers is related to the quality of the products offered, the quality of service to create customer satisfaction. This study aims to determine the effect of social status, product quality, and consumer satisfaction on the intention to repurchase Baper Milk Coffee in Metro City.The research design is quantitative research or verification research. The variables in this study are social status, product quality, and consumer satisfaction with repurchase intention. The population and research sample were consumers of Metro City Baper Milk Coffee with a total sample taken of 96 people. Data collection techniques using a questionnaire. The analytical tool used is data quality analysis and Multiple Linear Regression with the SPSS program.The results showed that social status, product quality, and customer satisfaction had a significant effect on consumer repurchase intentions. Simultaneous test results show that social status, product quality, and consumer satisfaction together have a significant effect on consumer repurchase intention.